AB0646 Determinants of quality of life in systemic sclerosis and patient's perception of their illness. (15th June 2017) - Groseanu, L; Balanescu, A; Predeteanu, D; Opris-Belinski, D; Bojinca, V; Saulescu, I; Borangiu, A; Mazilu, D; Constantinescu, C; Berghea, F; Ionescu, R
Abstract : Background: Systemic sclerosis (SSc) is a chronic multi-system autoimmune disease associated with disability and reduced quality of life. Objectives: The purpose of this study was to assess health-related quality of life and disease perception in a group of SSc patients. Methods: We performed a case-control study on 50 SSc patients from EUSTAR cohort 096. Socio-demographic data, disease characteristics and self-assessment questionnaires: Health assesment questionnaire (HAQ), EuroQol-5D (EQ5D) and the Brief Illness Perception Questionnaire were collected. Results: The group included 41 females, 31 limited SSc subsets. Medium HAQ value was 0.9 (0.6). Patients with higher Rodnan score (p=0.002), synovitis (p=0.02), late capillaroscopic pattern (p=0.02), muscle weakness (p=0.001), gastrointestinal involvement (p=0.01) and those on immunosuppressants (p=0.02) have a poor life quality. According to EQ-5D, the quality of life was related to specific organ involvement. 48% of the patients had some mobility problems, 6% were confined to bed; mobility was influenced by lung involvement (p=0.008), digital ulcers (p=0.03) and Medsger score (p=0.01). 48% of the patients had some self-care problems and 8% were not able to wash/dry themselves; self-care was influenced by the Rodnan score (p=0.02), diffuse subset (p=0.02), muscle weakness (p=0.03) and gastrointestinal involvement (p=0.021). 64% of the patients had some problems in performing usual activities and 16% were not able to perform them; the performance was influenced by disease subset (p=0.01), Medsger score (p=0.02), cardiac involvement (p=0.02) and the use of immunosuppressants (p=0.01). 52% of the patients had some and 38% had extreme pain/disconfort; 66% of the patients were moderately and 20% were extremly anxious/depressed. Both were related to digital ulcers (p=0.01, respectively p=0.045) The illness had a great impact on patients life 7.3 (2.5)/10. The main determinant was pulmonary fibrosis (p=0.04). The patients consider that their disease will continue for quite a long time 8.7 (2.6)/10. Most of the patiens do not feel to have a good control on their disease 6.3 (3.3)/10 and unfortunately they do not think that the treatment is very helpful 7.9 (2.7)/10. The intensity of the symptoms is quite severe 7.5 (2.7)/10, related to digital ulcers (p=0.04) and gastrointestinal involvement (p=0.02). Patients are very concerned about their disease 9.1 (2.3)/10, most of them being emotionally affected 7.6 (2.6). Conclusions: This study confirms the presence and magnitude of impaired life quality in patients with SSc with impact on mobility, self-care, usual activities. The major determinants were the extend of skin involvement, musculoarticular, gastrointestinal involvement and digital ulcers. Often patients are anxious/depressed, had a high pain intensity and the perception of this illness is pessimistic. References: Hudson M, Canadian Scleroderma Research Group Health-related quality of life in systemic sclerosis: a systematic review. Arthritis Rheum. 2009;61(8):1112–2. Frantz C et al. Impaired quality of life in systemic sclerosis and patient perception of the disease: A large international survey. Semin Arthritis Rheum. 2016;46(1):115–23. Disclosure of Interest: None declared